COMPARATIVE ANALYSIS ON THE QUALITY OF SEVERAL BREADS ASSORTMENTS AVAILABLE ON THE ROMANIAN MARKET AND ON THE TECHNOLOGICAL PROCESSES RELIABILITY - Radiana Maria TAMBA-BEREHOIU; Ciprian Nicolae POPA; Vasilica SIMION; Bogdan Ştefan NEDELCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Our investigations have focused on the analysis of several bread assortments manufactured by the largest producer in Romania, in terms of key quality parameters. There were analyzed four breads assortments coming from a local producer, namely Vel Pitar, as follows: whole wheat bread (500g), white bread (300 g), intermediate bread (300 g) and dark bread (300 g). Of each assortment were taken 15 samples from different batches. For each sample were analyzed: Weight (W, g), Moisture (M, %), Acidity (A, grade), Porosity (P, %), Elasticity (E %), Water activity (aW), Length (cm), Width (cm), Height (cm). We have identified highly significant statistical differences between varieties of bread (Student test). We find that all the significant correlations formed have particularized bread assortments, because of the fact that the assortments of bread did not show significant correlations between the same quality parameters. It is highlighted in this way, the differences between recipes and technological process. To conclude, we can say that the whole wheat bread and dark bread are most alike, in terms of quality characteristics, given that both had an increased fiber content. It was also noted the similarities of quality parameters in white and intermediate bread. All observed differences, with varying degrees of significance, constituted peculiarities of bread assortments taken for analysis.